2000
DOI: 10.2134/jeq2000.00472425002900040005x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Assessment of the Aquatic Toxicity of Multiple Chemical Mixtures

Abstract: Current approaches to the assessment of chemical hazards focus on toxicity studies with single, pure chemicals. In the environment, however, organisms are exposed to numerous pollutants simultaneously. We studied the toxicities of multiple mixtures of pesticides and antibiotics in algal and bacterial bioassays. The test mixtures were composed of 14 to 18 components with either identical or completely different specific mechanisms of action. The results reveal that reliable predictions of mixture toxicities can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
100
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(108 citation statements)
references
References 0 publications
3
100
0
Order By: Relevance
“…Conversely, the IA model predicts the interaction of dissimilarly acting toxicants (34,35) and was first proposed by Bliss in 1939 (Eq. 2):…”
Section: Mixture Modelsmentioning
confidence: 99%
“…Conversely, the IA model predicts the interaction of dissimilarly acting toxicants (34,35) and was first proposed by Bliss in 1939 (Eq. 2):…”
Section: Mixture Modelsmentioning
confidence: 99%
“…Several studies have shown that the combined effects of pesticides sharing a common mode of toxic action are best predicted by a concentration addition (CA) model (Faust et al 2000;Deneer 2000;Kudsk et al 2005;Belden et al 2007). According to the CA model, pesticide concentrations are first normalized for potency and then the total concentration of the mixture is calculated and used to predict mixture toxicity (Faust et al 2000).…”
Section: Estimating the Effects Of Mixtures Of Carbamate And Organophmentioning
confidence: 99%
“…Furthermore, ponds and pools are the preferred habitat of many amphibians, which are experiencing worldwide population declines for a variety of hypothesized reasons, including exposure to insecticides [11,12]. Amphibian populations are often exposed to a number of insecticides that vary in their chemical and toxic properties [13]. Moreover, amphibian tolerance to pesticides can be highly enigmatic, with tremendous variation across amphibian families [14], among species within families, and among populations [15].…”
Section: Introductionmentioning
confidence: 99%